(untitled) - Huke, Robert E. (Manila, 1963)
The completion of this book is a memorable event in scholarship. It deserves some special comment which the public may find interesting. It represents highly significant and rewarding developments which I feel very fortunate in understanding and sharing with Dr.Robert E. Huke, whose work on this book helps to advance greatly our knowledge of Philippine geography and simultaneouly demonstrates some of the best motivations and principles in the lives of scholars and of institutions devoted to scholarship and public education.
Keywords: Philippines,Philippines; Economic conditions,Điều kiện kinh tế; 1918-,1918-